1998
DOI: 10.1246/bcsj.71.483
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Properties of Unsymmetrically Substituted Bi- and Quaterthiophenes

Abstract: The unsymmetrically substituted bi- and quaterthiophene derivatives were synthesized. The unsymmetrically substituted bithiophenes carrying the electron-withdrawing substituent X on one of the outer thiophene rings exhibited the maxima of absorption bands at the longer wavelengths than the symmetrically disubstituted bithiophene derivatives, while the unsymmetrical quaterthiophenes had such maxima at the shorter wavelengths than the corresponding symmetrical ones. The trend of bathochromic shift of the longest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…One dimensionally extended OEP(M) -(DHBTh) n -OEP(M) derivatives (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) also bring about some finding for the present peculiar system. As derived from the previous study, 11 it is further confirmed that the Pd complexes as well as the Ni ones show the unique spectral features with simple regularity.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…One dimensionally extended OEP(M) -(DHBTh) n -OEP(M) derivatives (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) also bring about some finding for the present peculiar system. As derived from the previous study, 11 it is further confirmed that the Pd complexes as well as the Ni ones show the unique spectral features with simple regularity.…”
Section: Introductionsupporting
confidence: 54%
“…Thus, it is shown that all the compounds 8 -25 in both HH and TT series possess the ring currents of OEP(M) almost the same as those for 36 and 37, regardless of the number of DHBTh, exhibiting meso-H at around 9.4 ppm for the Ni complexes and 9.9 -10 ppm for the Pd complexes (Table 1). This result exactly indicates that all the DHBTh constituents in [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] have no abilities to perturb the ring current of OEP(M), similarly to the case for 1 -7. Such a structural property indicates that the area of influence from the anisotropic effect of OEP(M) could be estimated accurately by the chemical shift analysis of Th-H, because all the DHBTh constituent are fixed both independently and regularly with a rigid diacetylene linkage in one direction.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations